Benefits of performance improvement rehabilitation model for boxing elite - Bestinov, R. V.; Kolodeznikov, K. S.; Dmitriev, O. N. (Theory and Practice of Physical Culture, 2020)
Presently the sport community gives a high priority to the post-training rehabilitation process design and management models to secure high athletic performance; albeit many training systems are still dominated by the high-intensity trainings at sacrifice of the rehabilitation elements. Objective of the study was to rate benefits of a new performance improvement rehabilitation model for boxing elite with the punching power and speed rating elements.